Analysis of Oil and Fat Content in Palm Oil Industry Wastewater Gravimetric Analysis - Amelia, Dian; Wijayanti, Fitria; Legasari, Leni (ALKIMIA, 2023)
Wastewater is unused waste water and contains many substances that can pollute the environment and disturb the health of living things. One of the parameters of wastewater pollution that is found in everyday life is oil and fat. Oil and fat are one of the parameters in wastewater consisting of compounds that can pollute water bodies so that their concentration must be limited, because their impact can damage aquatic ecosystems, especially on water resources. Oil and fat are compounds that contain the main component, triglycerides. Triglycerides are molecules resulting from condensation between one glycerol and three fatty acids. Based on SNI 6989.10: 2011 from the Regulation of the Minister of Environment No.05 of 2014, states that the maximum concentration of oil and fat quality standards contained in wastewater from the palm oil industry is 25 mg/L. The results of the analysis that has been carried out show that the levels of oil and fat in the palm oil industry wastewater samples include In-let wastewater (12,4 mg/L), Out-let (8,4 mg/L), Up-stream (3,6 mg/L) and Down-stream   (6 mg/L) which have been tested and analyzed using the gravimetric method